Adolescent cognitive control and mediofrontal theta oscillations are disrupted by neglect: Associations with transdiagnostic risk for psychopathology in a randomized controlled trial. (June 2020) - Buzzell, George A.; Troller-Renfree, Sonya V.; Wade, Mark; Debnath, Ranjan; Morales, Santiago; Bowers, Maureen E.; Zeanah, Charles H.; Nelson, Charles A.; Fox, Nathan A.
Abstract: Children that have experienced psychosocial neglect display impairments in self-monitoring and controlling their behavior (cognitive control) and are at broad, transdiagnostic risk for psychopathology. However, the neural underpinnings of such effects remain unclear. Event-related mediofrontal theta oscillations reflect a neural process supporting cognitive control that may relate to transdiagnostic psychopathology risk. Recent work demonstrates reduced mediofrontal theta in rodent models of neglect; however, similar findings have not been reported in humans. Here, 136 children reared in Romanian institutions were randomly assigned to either a high-quality foster care intervention and placed with families or remained in institutions; 72 never-institutionalized children served as a comparison group. The intervention ended at 54 months; event-related mediofrontal theta and psychopathology were assessed at 12- and 16-year follow-up assessments. Institutional rearing (neglect) predicted reduced mediofrontal theta by age 16, which was linked to heightened transdiagnostic risk for psychopathology (P factor); no specific associations with internalizing/externalizing factors were present once transdiagnostic risk was accounted for. Earlier placement into foster care yielded greater mediofrontal activity by age 16. Moreover, foster care placement was associated with the developmental trajectory of mediofrontal theta across the adolescent period (ages 12–16), which was, in turn, associated with greater reductions in transdiagnostic risk across this same period. These data reflect the first experimental evidence that the development of mediofrontal theta is impacted by removal from situations of neglect in humans, and further characterizes the importance of studying developmental change in mediofrontal theta during the adolescent period.